WORKSHOP PERSIAPAN MENGHADAPI DUNIA KERJA DAN TEKNIK INTERVIEW BAGI SISWA KELAS XII SMKS BUDI ASIH TEBET JAKARTA SELATAN - Karya Bakti Kaban; Mira Firlana (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Vocational High School is a school that educates its students to be ready to enter the world of work. They are equipped with various knowledge and skills that can be used in the world of work.Class XII is the period when SMK students must stop playing around and take the time to study in order to pass school and state exams. After that focus on finding work. Entering the world of work is not as easy as turning the palm of the hand. Newly graduated SMK students have to take job entrance exams, and compete with people with higher education. Of course, vocational school graduates are starting to wonder to themselves, "can I be accepted to work here?"At that time what SMK graduates had to do was motivate and convince themselves that they could compete with those with higher education than them. Passion, brain, beauty, discipline, behavior and motivation are factors that influence success in the world of work. Motivation is a set of attitudes and values ​​that influence individuals to achieve specific things according to one's goals. While success is defined as success or luck. Motivation for success in the world of work is needed because it will encourage someone to further optimize their abilities in the world of work How can SMK graduates be successful in the world of work? How to find passion in the world of work? How do we motivate ourselves to stay focused on work when the mood is down? What is the professional ethics that must be carried out in the company? What are the tips and tricks so that SMK graduates can pass the job entrance test? How do you deal with the interview process when applying for a job?